Development of model training mentoring in improving assistant competence in the convection group of businesses - Djibu, Rusdin; Shofwan, Imam (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2019)
This research aims to develop a mentoring training model to improve the competence of the assistant in the convection group in the city of Gorontalo. The approach used in this research is qualitative. The methods used are research and development (R & D) which include the following activities: (1) Preliminary review of the initial condition of competence of convection assistants, (2) Development model Mentoring, (3) expert validation and revision, (4) implementation of the model , (5) test the effectiveness of the model, and (6) model recommendation. The results of Development Studies show: (1) initial condition of convection competence of the general do not follow the standards of convection assistant, because the convection assistant has not received training, (2) The development of training model mentoring to Increase the competence of convection assistants conducted through several steps; Conducting analysis of development needs, determining the elements to be developed, developing a mentoring model to improve quality and productivity, validating model development with non-formal education experts, educational practitioners Non-formal and peer, and compile the final model, (3) Implication model assistance is conducted thorough testing and testing model assistance. All these activities are done through stages; Planning, organizing, implementing, evaluating, and delivering results. (4) The development of a training model affects the effectiveness and efficiency of training implementation. Effectiveness tests are conducted through post-test. Research findings suggest that the training model of mentoring to improve the competencies developed by the convection Assistant is recommended for the interested parties.